Pengaruh Kerja Sama Antara Rumah Sakit dengan Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan Terhadap Jumlah Kunjungan Rumah Sakit di Indonesia - Iha Nursolihah; Dian Agnesa Sembiring; Sekar Ayu Runggandini (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
According to BPJS Kesehatan data, the number of health facilities that cooperate with BPJS Kesehatan does not necessarily increase, even in 2019 the achievements of the FKRTL that work together have decreased, even though every year NHI participants have increased. BPJS Kesehatan continues to try to optimize the NHI’s system so that the benefits can be felt by participants and health facilities as providers, one of which is an increase in hospital visits. This study aims to determine the effect of cooperation with BPJS Kesehatan on the number of hospital visits in Indonesia. This type of research is analytic observational with a cross-sectional study design. The research samples were all hospitals in Indonesia that were designated as referral hospitals and other hospitals were sampled using a sample size calculation. The selected sample was 532 hospitals. The statistical test results obtained a value of p = 0.0001 for all independent variables so that there was a significant difference in the average number of emergency patients, number of inpatients, number of outpatient visits, and number of laboratory visits between hospitals cooperating with BPJS Kesehatan and hospitals that are not partners with BPJS Kesehatan. Thus, there is an influence between cooperation with BPJS Kesehatan on the number of hospital visits in Indonesia.